A SYSTEM OF AUTOMATED GREENHOUSE FEEDING WITH CO2 - A. N. Makhmutov (Овощи России, 2017)
At present time, the significant deficiency of СО2 for plants cultivated in greenhouses is one of the factors limiting the photosynthesis and carbonate accumulation leading to decrement of vegetable plant productivity.  The development of necessary gas atmosphere inside greenhouses is the same as important as maintaining temperature regimes.  In  the  world,  there  are  different  solutions  for greenhouse feeding with СО2. Nowadays, the most effective and ecologically safe equipment for greenhouse feeding with СО2 is that provide, not only a smoke-like gas, but also a purified food quality carbon dioxide. This technology required system of gas pipe lines for greenhouses and system of automated control for gas feeding. Moreover it is necessary to install the storage facilities for liquid  carbonic  acid, gas generator, heating system and other   equipment.   Such   a   complex   for   automatic greenhouse feeding with СО2 ‘Kaskad’ has been worked out by OOO ‘Kaskad’ that has successfully developed the systems for carbon-dioxide feeding for 10 years. The system  that  combined  automatic  supplying  outcoming  gas from  boiler  station,  and liquid  СО2  injecting  into  greenhouse room was developed in 2015. The system enables to be integrated into the feeding liquid СО2 and existing system of supplying the outcoming  gas from boiling station.